Internalization of Characteristics and Assistance for Curriculum Development of Diniyyah “Sabilissalam” Madrasah Duri Slahung Ponorogo - Aprilia Dian Sukmawati; Muhammad Heriyudanta (Peneliti Teknologi Teknik Indonesia, 2022)
Internalization of Characteristics and Assistance for Curriculum Development of Diniyyah “Sabilissalam” Madrasah Duri Slahung Ponorogo